Pemanfaatan Media Film pada Materi Sejarah Pertumbuhan Ilmu Pengetahuan pada Masa Umaiyah untuk Mempertahankan Hasil Belajar Siswa Kelas VIII SMP Negeri 03 Tugu Trenggalek dalam Pembelajaran Daring Tahun Ajaran 2020/2021 - Konik'atin, Konik'atin (Jurnal Likhitaprajna, 2021)
Learning in the Covid-19 pandemic situation, all teachers are required to be able to present material using online methods, media and learning. The purpose of this study was to describe the learning outcomes of 8th grade students by using film media on the history of science during the Umaiyah period at State Junior High School 03 Tugu of Trenggalek during online learning. This type of research is Classroom Action Research. This study used two cycles by applying four steps, namely: (1) Plan; (2) act; (3) observe; and (4) reflect. The instruments used are observation and tests. The data analysis techniques used are (1) Qualitative Data Analysis Techniques, and (2) Quantitative Data Analysis Techniques. The results showed that in the first cycle there were 30 (75%) of the students who had met the minimum standard of completeness and 10 (25%) of the students did not meet the minimum standard of completeness. While in cycle 2 it was known that there are 36 (90%) meet the minimum completeness standard and only 4 (10%) of the students did not meet the minimum completeness standard.